The Effect of Regional Fiscal Policy on Economic Growth in North Sumatera - Laila Rohimah; Ahmad Albar Tanjung; Indah Permata Sari Pulungan (Journal of International Conference Proceedings (JICP), 2020)
The aim of this research is to evaluate and provide new evidence of the influence of regional fiscal policy with government expenditure instruments and tax revenue on economic growth in North Sumatra Province. The data used are quarterly data from 2011: 1 to 2017: 4 sourced from the Central Statistics Agency of North Sumatra Province (CSA). The analytical method used in this study is the error correction model (ECM) method. The findings of this study are that government expenditure (GE) has a positive and significant effect in the short and long term on the economic growth (PDB) of the province of North Sumatra during the study period. While tax revenue (TAX) in the long-run has a positive and significant effect, but in the short term, it has a positive but not significant effect on the economic growth (PDB) of the province of North Sumatra during the study period.